Optimal Income Tax Rates for the Korean Economy - 장용성 (14255, 2015)
Based on a quantitative, heterogeneous agent general equilibrium model, we compute the optimal tax rates for labor and capital incomes for the Korean economy. According to our model, a more progressive income tax schedule along with a higher capital tax r